Metabolic alterations in Strongyloidiasis stool samples unveil potential biomarkers of infection - Montanhaur, Allan Daniel Ribeiro Sotelo; Lima, Estela de Oliveira [UNESP]; Delafiori, Jeany; Esteves, Cibele Zanardi; Prado, César Corat Ribeiro; Allegretti, Silmara Marques; Ueta, Marlene Tiduko; Levy, Carlos Emílio; Catharino, Rodrigo Ramos (Elsevier, 2022)
Strongyloidiasis, a parasitosis caused by Strongyloides stercoralis in humans, is a very prevalent infection in tropical or subtropical areas. Gaps on public health strategies corroborates to the high global incidence of strongyloidiasis especially due to challenges involved on its diagnosis. Based on the lack of a gold-standard diagnostic tool, we aimed to present a metabolomic study for the assessment of stool metabolic alterations. Stool samples were collected from 25 patients segregated into positive for strongyloidiasis (n = 10) and negative control (n = 15) and prepared for direct injection high-resolution mass spectrometry analysis. Using metabolomics workflow, 18 metabolites were annotated increased or decreased in strongyloidiasis condition, from which a group of 5 biomarkers comprising caprylic acid, mannitol, glucose, lysophosphatidylinositol and hydroxy-dodecanoic acid demonstrated accuracy over 89% to be explored as potential markers. The observed metabolic alteration in stool samples indicates involvement of microbiota remodeling, parasite constitution, and host response during S. stercoralis infection.
Keywords: Biomarkers; Mass spectrometry; Metabolites; Metabolomics; Parasitic infection; Strongyloides stercoralis; Strongyloidiasis